The activation of directional stem cell motility by green light-emitting diode irradiation - Ong, Wei-Kee; Chen, How-Foo; Tsai, Cheng-Ting; Fu, Yun-Ju; Wong, Yi-Shan; Yen, Da-Jen; Chang, Tzu-Hao; Huang, Hsien-Da; Lee, Oscar Kuang-Sheng; Chien, Shu; Ho, Jennifer Hui-Chun (My University, 2013)
Light-emitting diode (LED) irradiation is potentially a photostimulator to manipulate cell behavior by opsin-triggered phototransduction and thermal energy supply in living cells. Directional stem cell motility is critical for the efficiency and specificity of stem cells in tissue repair. We explored that green LED (530 nm) irradiation directed the human orbital fat stem cells (OFSCs) to migrate away from the LED light source through activation of extracellular signal-regulated kinases (ERK)/MAP kinase/p38 signaling pathway. ERK inhibitor selectively abrogated light-driven OFSC migration. Phosphorylation of these kinases as well as green LED irradiation-induced cell migration was facilitated by increasing adenosine triphosphate (ATP) production in OFSCs after green LED exposure, and which was thermal stress-independent mechanism. OFSCs, which are multi-potent mesenchymal stem cells isolated from human orbital fat tissue, constitutionally express three opsins, i.e. retinal pigment epithelium-derived rhodopsin homolog (RRH), encephalopsin (OPN3) and short-wave-sensitive opsin I (OPN1SW). However, only two non-visual opsins, i.e. RRH and OPN3, served as photoreceptors response to green LED irradiation-induced OFSC migration. In conclusion, stem cells are sensitive to green LED irradiation-induced directional cell migration through activation of ERK signaling pathway via a wavelength-dependent phototransduction. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Cell motility; Light-emitting diode; Photosensitization; Stem cells; Wavelength